Neoliberalism: The Ideological Dilemma of Nepali Congress - Shahi, Ganesh Bahadur (Four Star Multidisciplinary Research Journal, 2025)
This comprehensive analysis examines the Nepali Congress (NC) party’s complex relationship with neoliberal economic policies over three decades of democratic transition. As Nepal’s dominant centrist force, NC has championed market liberalization, privatization, and international integration since the 1990s, positioning these reforms as essential for development. However, these policies have generated profound contradictions: entrenched inequality, agricultural decline, remittance dependency, and geopolitical vulnerability amid Sino-Indian rivalry. Drawing on political economy frameworks and empirical data, this study argues that NC’s embrace of neoliberalism has undermined its social democratic foundations while failing to deliver structural transformation. The party now faces an existential dilemma-maintaining elite alliances forged through neoliberal patronage or reclaiming its redistributive legacy to address widespread disillusionment with Nepal’s fragile democracy strained by chronic instability. Therefore, NC’s navigation of this dilemma will determine both the party’s survival and developmental trajectory of Nepal.